Gestão democrática do ensino público: narrativas sobre a escolha do diretor e a constituição do conselho escolar na autonomia da escola - Antunes, José Adilson Santos (2012)
This paper presents a reflection on the early Democratic Management of Public Education in Rio Grande do Sul, highlighting the process of constitution of the School Boards and the choice of state school principals from the analysis of the speeches of former directors who participated and / or coordinated, in practice, the democratization of the public school. A brief evaluation of management education, democratic management and school autonomy to seek the foundations of this work, the opportunity for a reflection on the meaning and importance of the participation of the segments of the school community in school management as a principle of democratic management. The interviews with teachers who played the role of school principals in different historical moments of the implementation process of democratic management of public education, made the trek reveal the importance of the participation of parents, students, faculty and staff in the management of public schools and strengthening the autonomy of the school, founded in the Constitutions and laws of education, whose main stronghold Law of Guidelines and Bases of National Education, LDBEN n. 9.394/96. The narratives focused since the proposed changes in school management in 1995, through the first process of nominating directors by the vote of the school community and the changes implemented in 2001 in the Democratic Management Act on Public Education, Law 10.576/1995, which reflected the electoral process in schools since 2003, reported the role of the School Board in school management and strengthening of school autonomy, especially in the financial aspect, emphasized the weakening of participation in some segments, especially parents, whose presence in school longer to be frequent to be sporadic in the process of making decisions spurred by the School Board, and stressed the need to improve the process of election of directors, respecting the differences between segments, valuing education professionals, whose commitment to the project's success proposed school is essential for the effective implementation of the plan indicated direction. And before that, a content analysis of the narratives, in rescuing the implementation process of the Democratic Management of Public Education, from two school realities in different historical moments, we seek to identify how the choice of the director and the establishment of the School Board are important strengthening the autonomy of educational institutions, with a focus on decision-making by the community.